The Role and Mechanism of Tanḍīḍ in Calculating the Zakat of Inventories - Shammout, Mohammad Marwan (Journal of Economic, Administrative and Legal Sciences, 2022)
Zakat is one of the five pillars of Islam, it is a mandatory to pay a specific proportion of specific wealth for specific people, and the inventories are considered one of this wealth that Zakat is required to be paid according to the views of most of the Islamic Schools and most likely Says, the weighted views for paying the value varied in how to evaluate inventories accurately and thus to determine the amount of Zakat, which makes the accountant or the donor to use estimation, so that the results are an approximation and nearly a precaution, and it is further complicated when calculating the Zakat of large commercial companies whose products vary and the size of their inventory increases, that is considered as one of the basic elements of its balance sheet, so that the evaluation would be undisciplined, which questions the results of the Zakat account. Therefore, this study was created, which aimed to research the method of evaluation based on measurement using the method of Tanḍīḍ according to the modern accounting thought of the evaluation according to the concept of net realisable value to be easily applied in the calculation of Zakat of inventory to prevent the existence of doubts in measurement and to reduce the difference of opinions of the estimators. The results of the study are considered in touch with reality by using mathematical equations that facilitate the work of calculating Zakat, which are recommended to be adopted and considered as a criterion in accounting for the Zakat of companies.